2023
DOI: 10.1002/fsn3.3356
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between total phenolic and flavonoid contents and biological activities of 12 ethanolic extracts of Iranian propolis

Abstract: Propolis is a resinous substance produced by honey bees that is very popular as a natural remedy in traditional medicine. The current research is the first study on the biological properties of ethanolic extracts of propolis (EEP) from several different regions (12) of Iran. Total phenolic and flavonoid contents (TPC and TFC) of Iranian EEPs were variable between 26.59-221.38 mg GAE/g EEP and 4.8-100.03 mg QE/g EEP. The DPPH scavenging assay showed all the studied EEP samples, except for the sample with the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 114 publications
1
10
1
Order By: Relevance
“…Antioxidants contained in propolis may protect against these diseases [ 29 , 30 ]. It has been shown that the high content of some flavonoids, such as quercetin, kaempferol, and galangin, affects the high antioxidant activity of propolis extracts [ 31 , 32 ]. The antioxidant capacity of flavonoids is mainly related to their chemical structure and, as with phenolic acids, is based on the O-H bond dissociation energy value [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants contained in propolis may protect against these diseases [ 29 , 30 ]. It has been shown that the high content of some flavonoids, such as quercetin, kaempferol, and galangin, affects the high antioxidant activity of propolis extracts [ 31 , 32 ]. The antioxidant capacity of flavonoids is mainly related to their chemical structure and, as with phenolic acids, is based on the O-H bond dissociation energy value [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 2021 ) reported that TPC and TFC values of Chinese propolis collected from five regions was ranged from 72.02 to 155.95 mg GAE/g, and 129.68 to 412.83 mg QE/g of ethanolic extracts, respectively. Whereas Iranian propolis samples showed TPC and TFC values ranged from 26.59 to 221.38 mg GAE/g and from 4.8 to 100.03 mg QE per g of ethanolic extract, respectively (Hafshejani et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic content (TPC) and the total flavonoid content (TFC) of PEs are given in (Hafshejani et al, 2023).…”
Section: Total Phenolic and Total Flavonoid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be attributed to the elimination of certain phenolic and flavonoid compounds during the nano-forming process. Hafshejani et al 45 reported that when comparing propolis collected from different regions of Iran, the propolis collected from Binalood Mountain has the highest amount of phenol and flavonoid compounds.…”
Section: Resultsmentioning
confidence: 99%